ARGUMENTATIVE ELEMENTS AND QUALITY OF MULTILINGUAL LEARNERS’ WRITING - Witri Oktavia (Universitas Negeri Padang, 2016)
As multilingual learners who have an array of linguistic and cognitive skills, Indonesian students have been exposed to various learning experiences intended to improve their metalinguistic awareness. They are expected to possess integrated competence of languages learnt. In light with this, this paper aims at analyzing students’ argumentative elements produced in their English argumentative writing, evaluating how far these elements contribute to the overall quality of their writing, and considering the influence of their status as multilingual learners. The result reveals that the students’ way in structuring their arguments influenced the quality of their writing. The developed writing were mostly produced by the students who were able to provide the equal weight of defending arguments and counter arguments which were elaborated in multiple arguments. Furthermore, since providing proper elaboration for the counterarguments was one of major problems in the students’ argumentative writing, the strategies to integrate arguments with counterarguments were also presented.